Pengaruh Digital Marketing Berbasis Social Media Tiktok terhadap Keputusan Pembelian Mi Sehat Lemonilo - Muhammad Alfian Aryadi; K. Y.S Putri (Avant Garde, 2022)
The development of information and communication technology makes the application of innovation easier, more effective and efficient. The development of information and communication technology also encourages a shift in people's habits in communicating. One company that uses social media as a means to promote and introduce their products is Lemonilo Indonesia Sehat, the company that owns the Lemonilo healthy noodle product. As a start-up that starts its business activities by utilizing online media, Lemonilo also utilizes social media that are widely used by the Indonesian people to carry out various marketing activities. The purpose of this study was to determine the effect of digital marketing based on Tiktok social media on purchasing decisions for Lemonilo healthy noodle products. The method used is a quantitative method with a correlational approach. The population contained in this study were students of the Communication Studies program at the State University of Jakarta batch 2019 as many as 82 students. Sampling in this study using probability sampling method by means of simple random sampling. The number of samples taken was 68 respondents based on calculations using the slovin formula. The results obtained in this study indicate that digital marketing carried out by Lemonilo has an influence on purchasing decisions for Lemonilo healthy noodle products. In this case the acquisition of T arithmetic shows a number greater than T table which means the dependent variable has an influence on the independent variable. In addition, the results obtained in the study show that the digital marketing variable has an influence of 28.5% on the purchasing decision variable.